Exploring the Influence of Cultural Norms on Consumer Behavior in a Globalizing and Digitalized Marketing Environment - Abashidze, Irakli; Khakhubia, Nino (European Scientific Journal, ESJ, 2026)
Consumer behavior in modern markets is largely shaped by cultural factors and the widespread use of digital platforms. Owing to globalization and the rapid evolution of social media, the phenomenon of consumer behavior has grown increasingly complex over the last decades. This presents significant challenges in making culturally informed decisions, particularly through the use of digital platforms. Accordingly, brands must navigate marketing environments by accounting for numerous factors that shape purchase decisions, electronic word-of-mouth (eWOM), user-generated content (UGC), and online reviews. Marketers face highly unpredictable landscapes where localization and adaptation are crucial prerequisites for maintaining competitiveness. Simultaneously, brands must assess the extent of influence exerted by culture and digital platforms. Thus, the dynamics of globalization, culture, and digital platforms constitute crucial aspects in effective marketing decision-making. As a narrative literature review, this study synthesizes contemporary academic contributions to examine and analyze the interplay between consumer behavior, cultural determinants, globalization, and digital platforms. It seeks to identify the main features of consumer behavior shaped by culture within globalizing marketing contexts. The objective of the study is to propose approaches for leveraging cultural factors through digital communication channels in globalizing marketing environments. The study concludes that digital platforms both promote global behavioral convergence and enable data-driven reinforcement of local cultural identities. Finally, the findings are summarized in relation to the stated objective and research questions.